CÁC PHỨC HỆ SINH THÁI BÀO TỬ PHẤN HOA TRONG TRẦM TÍCH HOLOCEN Ở ĐỒNG BẰNG NAM BỘ - Thuận, Đinh Văn; Dỹ, Nguyễn Địch (Vietnam Journal of Earth Sciences, 2017)
Holocene sediments have been formed duringthe past 10,000 years, in which there is no remarkable evolution in flora and fauna. They depend on the living condition of each taxon., i.e.once the environment changes, the species composition changes to adapt this, so Quaternary stratigraphical study, as well as Holocene one should be eco-stratigraphically dealt with. The ecological assemblages reflect the sedimentary environment of each period in each concrete area.The article presents the following problems :- Base and principle for dividing ecologicalassemblages of pollen and spore- Characteristics of ecological assemblages ofpollen and spore- There are 5 ecological assemblages of pollen and spore in the Holocene period at Nam Bo pain:+ Humid tropic-Fluvial Assemblage+ Humid tropic-Fuvio, swampy Assemblage+ Humid tropic-Fuvio, marine Assemblage+ Humid tropic-Marine, swampy Assemblage+ Humid tropic-Shallow marine Assemblage